Fabrication of a high-performance thin film polarizer using lyotropic chromonic liquid crystals using a high-resolution nanoscale template - Kim, Hyuk Jun; Jung, Woo-Bin; Jeong, Hyeon Su; Jung, Hee-Tae (Royal Society of Chemistry, 2017)
Lyotropic chromonic liquid crystals (LCLCs) have attracted attention for their potential applications as thin-film polarizers. Although it is well reported that template-assisted method can efficiently align LCLCs for thin-film polarizers, the polarizer performance using the technique has not been well demonstrated. In this study, we report for the first time that the high-resolution (similar to 10 nm) pattern was found to be able to overcome the issue of dead space in the channel, and the LCLC columns were well aligned along the nanoscale array. The nanoscale array templates were fabricated by secondary sputtering lithography, and the chromonic nematic phase of the LCLC materials were prepared by dissolving the hydrogen chloride salt of bis-(N, N-diethylaminoethyl)- perylene-3,4,9,10-tetracarboxylic diimide in deionized water. A polarizing performance was observed (79.1% DOP and 29.5% TT at 475 nm) using a nanoscale array template with a high resolution (similar to 10 nm) and a high aspect ratio (> 30). To further enhance polarizer performance, the combination of a nanoscale array template and mechanical shearing was exploited. With this combined route, an LCLC polarizer exhibiting a total transmission of 40.6% and a degree of polarization of 99.5% was obtained. Compared to mechanical shearing, nanoscale array templates were found to dominantly align highly mobile LCLCs.